2015
DOI: 10.4172/2376-0427.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Profile in Vitiligo

Abstract: Vitiligo is one of the disease which is yet to understand its pathogenesis, however many studies associate this disease as an autoimmune. Detection of autoimmune cells in the serum, lesional and perilesional area of vitiligo patients gives more insight on the disease mechanism. Presence of autoantibodies against melanocytes antigens in vitiligo patients indicates an autoimmune involvement in the aetiology of the disease. Identification and characterization of vitiligo autoantibodies would pave the way for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 65 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Among the hypermethylated genes, we found those for a G-protein coupled receptor ( GRL101 ), a target of rapamycin complex 2 subunit ( MAPKAP1 ), an enolase ( enolase-4 ), sodium/potassium/calcium exchanger 1 and a perlucin-like protein. MAPKAP1 (TOR signaling pathway) promotes dark epithelial pigmentation ( Liu et al, 2017 ), GRL101 (rhodopsin signaling pathway) is an ortholog of the pigment dispersing factor ( Tanaka et al, 2014 ), and enolase (glycolysis/gluconeogenesis pathway) is a biomarker of vitiligo, a human pigmentation disorder affecting melanocytes ( Hamid et al, 2015 ). Perlucin is a well-known matrix protein found in the nacreous layer of the pearl oyster shell ( Joubert et al, 2010 ) with a function in the biomineralization process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the hypermethylated genes, we found those for a G-protein coupled receptor ( GRL101 ), a target of rapamycin complex 2 subunit ( MAPKAP1 ), an enolase ( enolase-4 ), sodium/potassium/calcium exchanger 1 and a perlucin-like protein. MAPKAP1 (TOR signaling pathway) promotes dark epithelial pigmentation ( Liu et al, 2017 ), GRL101 (rhodopsin signaling pathway) is an ortholog of the pigment dispersing factor ( Tanaka et al, 2014 ), and enolase (glycolysis/gluconeogenesis pathway) is a biomarker of vitiligo, a human pigmentation disorder affecting melanocytes ( Hamid et al, 2015 ). Perlucin is a well-known matrix protein found in the nacreous layer of the pearl oyster shell ( Joubert et al, 2010 ) with a function in the biomineralization process.…”
Section: Resultsmentioning
confidence: 99%
“…Enolase-4 is another candidate gene displaying hypomethylation at 30 m. Enolases are metalloenzymes involved in glycolysis and glycogen storage. One study reported a correlation between enolase activity and pigmentation: Hamid et al (2015) showed that patients with vitiligo (a pigmentation disorder affecting melanocytes and inhibiting pigment synthesis) synthesize antibodies directed against enolases. Since their discovery, enolases have been used as biomarkers for the diagnosis, treatment, and monitoring of vitiligo ( Hamid et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations